Case Report: Significant Response to the Combination of Lenvatinib and Immune Checkpoint Inhibitor in a Patient With Heavily Pretreated Metastatic Triple Negative Breast Cancer - Lee, Jin Sun; Yost, Susan E.; Yuan, Yuan (Frontiers in Oncology, 2021)
Background: Triple negative breast cancer (TNBC) has poor prognosis without targetable mutations. The combination of lenvatinib and pembrolizumab has shown clinical activity in different types of solid tumors. Case presentation: We report a case of one patient with metastatic TNBC who has been heavily pretreated. The patient had been treated with multiple lines (> 8 lines) of chemotherapy without durable clinical responses. Her tumor regressed significantly under the combination of lenvatinib and immune checkpoint inhibitor, and remains stable for 10 months. Conclusions: The combination of lenvatinib and immune checkpoint inhibitor may have significant clinical activity in selective patients with heavily pretreated metastatic TNBC.